2013
DOI: 10.1007/s13762-013-0385-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variations in methane emissions from natural wetlands in China

Abstract: Natural wetlands are thought to be one of the largest natural sources of atmospheric methane concentrations. Although numerous studies referred to the rate of methane fluxes in different geophysical regions, only a few had estimates of the overall geographical methane emissions in China. This study estimated the spatial variations of annual methane emissions with the pixel size of 1 km 9 1 km from natural wetlands, excluding water surface, in China. The natural wetland areas were extracted from the database of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…Jin [60] estimated an area of 13.4 M ha based on the soil wet extent [76]. Our area estimate was based on remote sensing data [15] and was consistent with both Xu and Tian's study [62] and Zhang and Jiang's study [74].…”
Section: Estimates Of the Regional Ch 4 Emissions From The Tpsupporting
confidence: 81%
See 1 more Smart Citation
“…Jin [60] estimated an area of 13.4 M ha based on the soil wet extent [76]. Our area estimate was based on remote sensing data [15] and was consistent with both Xu and Tian's study [62] and Zhang and Jiang's study [74].…”
Section: Estimates Of the Regional Ch 4 Emissions From The Tpsupporting
confidence: 81%
“…The variation may have been due to the estimation method. Most previous studies used the survey wetland area (e.g., [18,19,74]). Jin [60] estimated an area of 13.4 M ha based on the soil wet extent [76].…”
Section: Estimates Of the Regional Ch 4 Emissions From The Tpmentioning
confidence: 99%
“…The simulation with Niu2012 suggested that China's wetlands emitted 3.86 ± 1.09 Tg CH 4 yr −1 in the 2000s, which falls within the reported range of previous studies (Table ). It was found that NE China plays a dominant role of 49% of CH 4 emissions, while the TP contributes only 25%, consistent with most simulations using various wetland maps in the present study (except GLWD) and other previous studies [ Ding et al, ; Xu and Tian , ; Zhang and Jiang , ]. In contrast, a previous bookkeeping survey [ Chen et al, ] estimated that the TP plays a dominant role of 45.6% of China's CH 4 emissions with 1.25 Tg CH 4 yr −1 , while NE China contributes only 25.3% with 0.59 Tg CH 4 yr −1 .…”
Section: Discussionmentioning
confidence: 99%
“…Building on these measurements, several groups conducted bookkeeping estimations of the CH 4 budget of China's natural ecosystems. However, a huge range has been reported for the magnitude of wetland CH 4 emissions, i.e., 1.30 to 5.71 Tg CH 4 yr −1 [ Wang et al, ; Ding et al, ; Cai , ; Chen et al , ; Zhang and Jiang , ]. For CH 4 uptake, Cai [] estimated that grasslands and forests take up −1.73 and −0.60 Tg CH 4 yr −1 , respectively, while Wang et al 's [] estimates of −0.65 and −0.68 Tg CH 4 yr −1 , respectively, were much less, also indicating significant uncertainty.…”
Section: Introductionmentioning
confidence: 99%
“…Methane is released into the atmosphere through: molecular diffusion (peat pore spaces), ebullition (a process where bubbles in gas are formed from a dissolved state in water and channel their way to surface to the atmosphere) at the water table interface, and vascular plants with aerenchymous porous tissues which transport gases through plant roots into the atmosphere (Dinsmore, Skiba, Billett, & Rees, 2009;Watanabe, Purwanto, Ando, Kakuda, & Jong, 2009;Farmer, Matthews, J. Smith, P. Smith, & Singh, 2011;Zhang & Jiang, 2014). Methane can also be emitted through non-microbial CH 4 production from soil organic matter under favorable conditions such as high temperature, UV radiation, and reactive oxygen species (B. Wang, Hou, Liu, & Z. Wang, 2013).…”
Section: Introductionmentioning
confidence: 99%